Research on the Innovation Path of Enterprise Management Models in the Era of Big Data - Zheng, Wenwei (Transactions on Economics, Business and Management Research, 2024)
In the context of the big data era, various new technologies have been widely applied, bringing new opportunities and challenges to business development. To develop steadily in fierce competition, enterprises must keep pace with the times and innovate based on traditional management models. Big data, characterized by its large volume, diverse types, fast processing speed, and low value density, has become a crucial engine for business development. It enables enterprises to precisely grasp market dynamics, optimize decision-making processes, and enhance operational efficiency, thereby bringing significant economic benefits and competitive advantages to businesses. However, facing the challenges of big data, enterprises also encounter numerous issues and difficulties, such as effectively collecting, processing, and analyzing massive data, ensuring data security and privacy, and cultivating talent with big data skills. Thus, enterprises need to adopt scientifically effective measures to fully leverage the advantages of big data technology, improve management quality, and lay a solid foundation for the healthy and sustainable development of businesses.